2010
DOI: 10.1088/2041-8205/725/2/l172
|View full text |Cite
|
Sign up to set email alerts
|

THE HDO/H 2 O RATIO IN GAS IN THE INNER REGIONS OF A LOW-MASS PROTOSTAR

Abstract: The HDO/H 2 O abundance ratio is thought to be a key diagnostic for the evolution of water during the star and planet formation process and thus for its origin on Earth. We here present millimeter-wavelength high angular resolution observations of the deeply embedded protostar NGC 1333-IRAS4B from the Submillimeter Array targeting the 3 12 -2 21 transition of HDO at 225.6 GHz (E u = 170 K). We do not (or only very tentatively) detect the HDO line toward the central protostar, contrasting the previous prominent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 26 publications
6
54
1
Order By: Relevance
“…The deuteration fraction observed in high-mass hot cores is typically HDO/H 2 O ≤ 10 −3 (Jacq et al 1990;Gensheimer et al 1996;Helmich et al 1996), although higher values (∼10 −2 ) have recently been found for Orion (Persson et al 2007;Bergin et al 2010). This ratio has also been estimated in the inner envelope of low-mass protostars such as IRAS 16293-2422 (Parise et al 2005) at about 3%, NGC 1333-IRAS4B (Jørgensen & van Dishoeck 2010) with an upper limit of 0.06%, and NGC 1333-IRAS2A (Liu et al 2011) with a lower limit of 1%. Deuterated water has also been sought in ices towards several protostars, and has allowed Dartois et al (2003) and Parise et al (2003) to obtain upper limits of solid HDO/H 2 O from 0.5% to 2%.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…The deuteration fraction observed in high-mass hot cores is typically HDO/H 2 O ≤ 10 −3 (Jacq et al 1990;Gensheimer et al 1996;Helmich et al 1996), although higher values (∼10 −2 ) have recently been found for Orion (Persson et al 2007;Bergin et al 2010). This ratio has also been estimated in the inner envelope of low-mass protostars such as IRAS 16293-2422 (Parise et al 2005) at about 3%, NGC 1333-IRAS4B (Jørgensen & van Dishoeck 2010) with an upper limit of 0.06%, and NGC 1333-IRAS2A (Liu et al 2011) with a lower limit of 1%. Deuterated water has also been sought in ices towards several protostars, and has allowed Dartois et al (2003) and Parise et al (2003) to obtain upper limits of solid HDO/H 2 O from 0.5% to 2%.…”
Section: Introductionmentioning
confidence: 68%
“…However, this ratio of a few percent does not seem typical of all the Class 0 protostars since an upper limit of 6 × 10 −4 has been determined in the inner part of the envelope of the lowmass protostar NGC 1333-IRAS4B (Jørgensen & van Dishoeck 2010). The determination of the water deuterium fractionation in a larger sample of Class 0 protostars would allow us to know, from a statistical point of view, whether the HDO/H 2 O ratio is A132, page 10 of 12 rather about 10 −4 −10 −3 as observed in the NGC 1333-IRAS4B protostar, in comets (∼3 × 10 −4 ; e.g.…”
Section: Discussionmentioning
confidence: 93%
“…Study (1) Inner HDO/H 2 O ratio Outer HDO/H 2 O ratio Observations (2) Modeling (3) IRAS 16293-2422 a 3 × 10 −2 ≤2 × 10 −3 HDO: IRAM (4), JCMT (1) 1D, non-LTE H 16 2 O: ISO (11) b 4 × 10 −3 -5.1 × 10 −2 3 × 10 −3 -1.5 × 10 −2 HDO: HIFI (9), IRAM (3), JCMT (1) 1D, non-LTE H 18 2 O: HIFI (5) Jørgensen & van Dishoeck (2010a). (2) This column shows which tracers are used to determine the HDO/H 2 O ratios, which telescopes the analysis is based on, and how many detected lines (number into brackets) of each tracer are used.…”
Section: Sourcementioning
confidence: 99%
“…The notation IRAM refers to the single-dish 30 m-telescope. The star ( * ) shows that the modeling of the water lines was not carried out in the study quoted in Col. 2, but come, as explained in the text, from the following papers: Jørgensen & van Dishoeck (2010a); Persson et al (2012); Taquet et al (2013a); Mottram et al (2013). (3) This column describes the type of modeling used to determine the HDO/H 2 O ratio: 0D or 1D structure and LTE or non-LTE analysis.…”
Section: Sourcementioning
confidence: 99%
See 1 more Smart Citation